1993
DOI: 10.3171/jns.1993.78.5.0695
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive lumbar laminectomy for spinal stenosis

Abstract: A total of 258 consecutive decompressive lumbar laminectomies performed on 244 individuals presenting with spinal stenosis were analyzed retrospectively. Spinal fusion was avoided in all but two patients. Outcome in terms of pain relief and return to normal activity was evaluated in two stages, one derived from patient charts and having a relatively short-term follow-up time (mean 8.4 months) and a second derived from patient responses to a questionnaire (which also scored for satisfaction with the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
5
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 29 publications
3
71
5
5
Order By: Relevance
“…Silvers et al specifically investigated outcomes following decompressive laminectomy for patients with DLS. 44 Two hundred fifty-eight patients were included, 12 of whom had DLS. The mean age of the 12 patients undergoing laminectomy for DLS was 69 years, and there was a 100% relief in pain and 100% return to normal activity reported in the short-term follow-up (mean 8.4 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silvers et al specifically investigated outcomes following decompressive laminectomy for patients with DLS. 44 Two hundred fifty-eight patients were included, 12 of whom had DLS. The mean age of the 12 patients undergoing laminectomy for DLS was 69 years, and there was a 100% relief in pain and 100% return to normal activity reported in the short-term follow-up (mean 8.4 months).…”
Section: Discussionmentioning
confidence: 99%
“…24,35,43,44,46 Previous studies have indicated that laminectomies (Fig. 1C) can cause impairment of the facet joints, resulting in segmental instability.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Silvers et al in a retrospective study of 258 consecutive patients that underwent decompressive lumbar laminectomies observed no significant correlation between employment status and clinical outcomes (9). Similarly, Bourne et al in another retrospective study of 1,703 patients who underwent primary total knee arthroplasty, found no significant differences in postoperative satisfaction based on perioperative employment status (10).…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective study of 244 patients with LSS between 30 and 87 years treated with laminectomy, Silver et al reported a complication rate of 22%. The authors found no age-related differences in outcomes [23]. Ragab et al compared their results from a retrospective analysis of 118 patients (over 70 years of age) with the results in other reports.…”
Section: Discussionmentioning
confidence: 95%